"It doesn't work at all, that's my experience": Swedish forensic interviewers' views on interpreter-mediated child interviews. (May 2022) - Ernberg, Emelie; Magnusson, Mikaela; Koponen, Linnea; Landström, Sara
Abstract: Background: Legal practitioners have expressed concerns regarding the quality of interpreter-mediated forensic interviews with child witnesses. Objective: This mixed-methods study aimed to examine Swedish forensic interviewers' experiences of conducting child interviews via a language interpreter. Participants and setting: Forty-one forensic interviewers from the Swedish Police Authority with experience conducting interpreter-mediated child interviews participated in a digital survey. Methods: Their responses were analyzed using both qualitative (thematic and content analyses) and quantitative (descriptive and inferential statistics) approaches. Results: The forensic interviewers' general experiences of conducting interpreter-mediated child interviews were negative. Limited access to authorized legal interpreters and doubts regarding the accuracy of interpretation were described as major obstacles in these investigations. The presence of an interpreter could negatively impact children's disclosure process and limit their chances of expressing their views during legal proceedings. Conclusions: According to Swedish forensic interviewers, the quality of interpreter-mediated child interviews urgently needs to be addressed. Our results are consistent with previous surveys from Australia and the United States, highlighting the international relevance of these topics. Future improvements are vital to ensure that all children are provided an equal right to be heard during criminal investigations, regardless of the native language. Highlights: Swedish police report poor quality of interpreter-mediated child interviews. Limited access to qualified interpreters was seen as a considerable problem. Interpreters must translate interviews without being suggestive or uncomfortable. The quality of interpreter-mediated child interviews must be addressed urgently. Video-conference technology may be an option to phone interpretation.